Lowering Caveolin-1 Expression in Human Vascular Endothelial Cells Inhibits Signal Transduction in Response to Shear Stress - van der Meer, A. D. (Hindawi Publishing Corporation, 2009)
Vascular endothelial cells have an extensive response to physiological levels of shear stress. There is evidence that the protein caveolin-1 is involved in the early phase of this response. In this study, caveolin-1 was downregulated in human endothelial cells by RNAi. When these cells were subjected to a shear stress of 15 dyn/cm(2) for 10 minutes, activation of Akt and ERK1/2 was significantly lower than in control cells. Moreover, activation of Akt and ERK1/2 in response to vascular endothelial growth factor was significantly lower in cells with low levels of caveolin-1. However, activation of integrin-mediated signaling during cell adhesion onto fibronectin was not hampered by lowered caveolin-1 levels. In conclusion, caveolin-1 is an essential component in the response of endothelial cells to shear stress. Furthermore, the results suggest that the role of caveolin-1 in this process lies in facilitating efficient VEGFR2-mediated signaling.